PUBLIC SERVICE TRANSFORMATION: POLICY ANALYSIS THROUGH APPARATUS RESOURCE REFORM - Murni, Hari Nur Cahya; Nurfurkon, Ardika; Uang, Dedy Pribadi; Sadmoko, Rudi (Jurnal Kebijakan Pemerintahan, 2023)
Abstract This research discusses transformation in public services through policy analysis, with a focus on apparatus resource reform. This research aims to understand the impact and implications of human resource reform efforts in improving the quality of public services. Through a literature study approach, this research examines policy changes related to the selection, development and management of the public apparatus. This study uses a qualitative approach with a literature study method using secondary data by analyzing the transformation of public services in policy analysis through apparatus resource reform. The results of the analysis show that apparatus resource reform plays a crucial role in improving the capacity, integrity, and performance of public apparatus in public services. The findings of this study contribute significantly to the understanding of the importance of public service transformation in apparatus resource reform policy. The implications of this study can serve as a foundation for decision-makers in designing and implementing more effective policies in the context of public services in the future. Keywords: Public Service Transformation, Policy Analysis, Apparatus Resource Management Reformation.